USAHA CATERING OKE LA BEB GO ONLINE - Imanuel Deny Krisna Aji; Hilda Yunita Wono; Kuncoro Dewi Rahmawati; Gabriela Laras Dewi Swastika; Monika Teguh; Dheandra Mutiara Kayana (JPM17: Jurnal Pengabdian Masyarakat, 2020)
Made Subdistrict of Sambikerep, Surabaya is an area that is very close to Ciputra University campus building complex which is only about 3 km away.  The large number of migrants living in the area ranging from those who work in offices and students is a huge opportunity for residents of the Made Subdistrict to open catering business. This was the main reason underlying Ms. Alfiah to open a heavy food supply business. Ms. Alfiah is a housewife who loves cooking. Come from Lamongan Regency and has lived in the Made Subdistrict area for quite a long time. The problems faced by the business partners of Okay La Beb Catering are limited marketing: The catering business owner Oke La Beb has not implemented a marketing strategy that reaches more customers, the technology used is not maximal, often there are no transactions simply because she does not have any knowledge how to use technology for marketing. The solution is to provide basic knowledge of marketing strategies through integrated marketing communication, guiding the use of digital technology in marketing communications. Through community service activities conducted, Ms. Alfiah can use online media, namely Whatsapp (personal messenger) and (Instagram) social media in marketing. Keywords: online media, catering, digital technology, marketing communication